Time since invasion is not associated with the competitive effects of an alien herb - Prass, Marju; Ramula, Satu; Hamberg, Leena; Setälä, Heikki; Kotze, D. Johan (Springer Nature, 2025)
Whilst temporal dynamics of the abundance of invasive alien species has gained interest, less is understood about complex interactions determining their impacts on, e.g., how coexistence mechanisms and the resulting ecological impact of alien species change with time. Using the invasive nitrogen-fixing Lupinus polyphyllus (lupine) and its native competitor Leucanthemum vulgaris (daisy), we investigated the effect of time since invasion on the growth of both plants, including lupine’s allelopathic effects on daisy. We set up a full-factorial greenhouse experiment that utilised activated carbon to neutralise putative allelopathic compounds in the soil in relation to non-treated soils. The used field soils with natural microbial communities and abiotic soil properties were exposed to lupine for ca. 5 years, 10 years or 15 years, or had no known prior exposure (controls). Lupine significantly suppressed the growth of daisy in the first month and its final biomass. However, lupine’s allelopathy did not appear to be the cause for the suppression of daisy seedlings that were grown next to lupine for two months. In addition, while the biomass of daisy benefitted from growing in previously lupine-invaded soils, both daisy and lupine, and their coexistence were not affected by the time soil was exposed to lupine. These results demonstrate that while time since invasion could be important for ecological impacts of some invasive alien plants or in older invasions, the suppressive effect of the invasive lupine on 1–3-month-old daisy was immediate and stable.
Keywords: time since invasion; soil legacies; invasion history; invasive plants; Lupinus polyphyllus; competition